(untitled) - Janna, William S. (Boca Raton, 2010)
A time-tested book that has proven useful in various fluid mechanics and turbomachinery courses, this volume assumes knowledge of calculus and physics in its use of mathematics to model physical principles in fluid mechanics. Among its many useful features, this book: Updates advances and relevant examples; Introduces concepts of fluid statics and control/volume approach of determining flow; Carefully explains topics using step-by-step examples; Emphasizes applications areas, with extensive resources for design problems; Uses both SI units and British gravitational units; Includes computer and design problems formulated for use with a spreadsheet in any of the traditional programming languages
Keywords: Cơ học chất lỏng,Fluid mechanics